2003
DOI: 10.1111/1467-9663.00252
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising the ‘competitive’ strategies of rural manufacturing SMEs

Abstract: Recent research attributes rural industrialisation to the enhanced competitive performance of rural small and medium-sized enterprises (SMEs). Central to much of this work has been a desire to acknowledge empirical diversity in business behaviour and performance between different rural spaces. Drawing on the tenets of critical realism the authors develop a conceptual framework which permits the diversity of behaviour exhibited by rural SMEs to be more fully recognised and understood. This highlights the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…Keeble and Tyler (1995) in their studies, for example, found rural firms to be overwhelmingly independent, locally owned and locally managed relative to their urban counterparts. There also is evidence that they are both younger and smaller than urban firms (Keeble and Nachum, 2002;Jarvis and Dunham, 2003) and that most rural new firm founders are in-migrants to the area (Mitchell and Clark, 1999;Courtney and Moseley, 2008) rather than, by contrast to urban firms, from with the locality in which the firm was founded.…”
Section: The Sub-national Review: Implications For Rural Areasmentioning
confidence: 99%
“…Keeble and Tyler (1995) in their studies, for example, found rural firms to be overwhelmingly independent, locally owned and locally managed relative to their urban counterparts. There also is evidence that they are both younger and smaller than urban firms (Keeble and Nachum, 2002;Jarvis and Dunham, 2003) and that most rural new firm founders are in-migrants to the area (Mitchell and Clark, 1999;Courtney and Moseley, 2008) rather than, by contrast to urban firms, from with the locality in which the firm was founded.…”
Section: The Sub-national Review: Implications For Rural Areasmentioning
confidence: 99%
“…2010). New understandings of competitiveness and conceptualizations of a new rural economy have underlined the importance of strategic investments and supportive public policy (Jarvis and Dunham 2003; Markey et al. 2008a).…”
Section: Section Ii: Emergent Issuesmentioning
confidence: 99%
“…They have looked at individual influences (NORTH, 1998) and several influences simultaneously to try and determine their relative strength (KEEBLE and TYLER, 1995;NORTH and SMALLBNONE, 2000). Methodologies and the geographical scale of assessments have been equally diverse, with use being made of national datasets (FOTHERGILL and GUDGEN, 1982), bespoke numeric (GALLOWAY and MOCHERIE, 2005) and attitudinal (KEEBLE and NACHUM, 2002) questionnaires and more in depth qualitative surveys (JARVIS and DUNHAM, 2003), each with their own legitimacy. 2 Such 'quality of life' factors were first noted as a locational determinant in America in the 1950s (GREENHUT, 1956;TIEBERT, 1957).…”
Section: Different Characteristics Of Rural Businessesmentioning
confidence: 99%